PHILOSOPHICAL AND LEGAL BASIS OF MARRIAGE RELATIONS BETWEEN THE UZBEK PEOPLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The legal regulation of marriage is a transformative legal reality in society. The pursuit of the opposite sex, the regulation of sexual relations, in accordance with the norms of international law and, most importantly, taking into account the national mentality, the location of the natural landscape - this means that human rights are fully respected. The establishment of a special regulation on the age of marriage is considered as a legal concern for the families created in the society. The article describes the legal and philosophical basis of the Uzbek people's marital relationship